2020
DOI: 10.23887/ijssb.v4i2.24200
|View full text |Cite
|
Sign up to set email alerts
|

Praktek Tradisi Belis Dalam Adat Perkawinan di Desa Aiteas (Studi Post-Marital Residence Antara Matrilokal dan Neolokal)

Abstract: Penelitian ini berfokus pada posisi laki-laki dan perempuan terkait post-marital residence dalam praktek belis di Desa Aiteas bagi pengantin yang sesudah menikah tinggal (matrilokal) dan yang tidak tinggal bersama keluarga perempuan (neolokal). Penelitian menggunakan pendekatan deskriptif kualitatif. Data diperoleh melalui wawancara dan observasi. Penelitian dilakukan di Desa Aiteas, Posto Administrativu Manatuto, Municipio Manatuto, Timor Leste. Berdasarkan hasil penelitian, praktek perkawinan di Desa Aiteas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…7 This practice is more or less influenced by matriarchal power. 8 However, it could change and develop according to local traditions. A case in China showed that these changes occurred due to the perceived costs and benefits of its practice, as well as the influence of other families' lifestyle in the community.…”
Section: Matrilocalitymentioning
confidence: 99%
“…7 This practice is more or less influenced by matriarchal power. 8 However, it could change and develop according to local traditions. A case in China showed that these changes occurred due to the perceived costs and benefits of its practice, as well as the influence of other families' lifestyle in the community.…”
Section: Matrilocalitymentioning
confidence: 99%